Effect of Service Quality and Ease of Use Perception on Public Satisfaction of GoBis (Golek Bis) Suroboyo Application Users - Millensyah, Erwing Wahyu (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2025)
Effect of service quality and ease of use perception on public satisfaction with the GoBis (Golek Bis) application in Surabaya. This study employs a quantitative approach by distributing questionnaires to 400 respondents who are active users of the application. The results of multiple linear regression analysis indicate that both independent variables significantly affect user satisfaction. However, ease of use perception shows a stronger impact than service quality. This study addresses the gap in previous research, which has largely focused on technical usability and interface design of the GoBis application, by examining the direct effects of service quality and ease of use perception on public satisfaction. The findings provide practical insights for the Surabaya City Government to enhance GoBis through improved usability, integrated payment systems, accurate real-time information, and responsive services, thereby strengthening public satisfaction and loyalty toward smart transportation services.